2013
DOI: 10.3109/13693786.2013.788257
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory marker profiles in an avian experimental model of aspergillosis

Abstract: Aspergillosis is a common infection in avian species, but can be a challenge to diagnose. Inflammatory markers have been successfully used in mammals for diagnostic and monitoring purposes of various diseases. The aim of this study was to identify inflammatory markers that could aid in the diagnosis of aspergillosis in an avian species. Five-week-old Japanese quail were infected experimentally with Aspergillus fumigatus, and inflammatory markers were measured in plasma. In addition, lung tissues were cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…84,87,88 Results from the recent research investigations indicated that in quail infected with A. fumigatus, the SAA levels did not differ from the control birds but the HP levels were lower. 88 Moreover, HP levels were lower in infected quail which died than in infected survivors. 88 In contrast to decreases in HP, SAA increased in falcons diagnosed with fungal airway infection.…”
Section: Acute Phase Proteins (Apps) Evaluationmentioning
confidence: 89%
See 1 more Smart Citation
“…84,87,88 Results from the recent research investigations indicated that in quail infected with A. fumigatus, the SAA levels did not differ from the control birds but the HP levels were lower. 88 Moreover, HP levels were lower in infected quail which died than in infected survivors. 88 In contrast to decreases in HP, SAA increased in falcons diagnosed with fungal airway infection.…”
Section: Acute Phase Proteins (Apps) Evaluationmentioning
confidence: 89%
“…88 Moreover, HP levels were lower in infected quail which died than in infected survivors. 88 In contrast to decreases in HP, SAA increased in falcons diagnosed with fungal airway infection. 87 In another falcon study, no significant increases of SAA and HP levels were identified in the control animals, but were found in adult (75%) and juvenile falcons (100%) which developed granulomas after experimental infection.…”
Section: Acute Phase Proteins (Apps) Evaluationmentioning
confidence: 98%
“…Understanding the way in which free-living animals modulate their response to cope with pathogens is therefore of great ecological relevance and might even provide conservation practitioners with tools to predict the impact of a pathogen on fitness traits. For example, a previous study found that the concentration of haptoglobin (an inflammation-inducible protein) was lower in Japanese quail ( Coturnix japonica ) that died from Aspergillus fumigatus infection in comparison with individuals that have survived (Goetting et al ., 2013) and showed how haptoglobin may be used to describe survival probabilities (Goetting et al ., 2013). Moreover, as the levels of natural antibodies and complement in small blood samples provide information about immunocompetence (Matson et al ., 2005), these markers have been used to quantify the innate immunity of vertebrates in stressful conditions (Hegemann et al ., 2013; Vermeulen et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is an urgent need to identify markers associated with herpesvirus infections that can be used for the assessment of health status in order to strengthen conservation strategies. For instance, as infectious diseases may induce inflammation (Eckersall et al ., 2001; Gånheim et al ., 2007; Grau-Roma et al ., 2009; White et al ., 2012), inflammatory markers might be a tool to diagnose and monitor animal diseases (Jain et al ., 2011; Goetting et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…During IPA, angioinvasion results in hemorrhagic infarction and release of hemoglobin. The importance of the host response of releasing Hp to bind hemoglobin during invasive aspergillosis was recently reported by Goetting et al, who found that plasma iron was significantly increased in infected animals (13). Fusarium infection also has been associated with elevated Hp concentrations in the tears of patients with fusarial keratitis (14).…”
Section: Discussionmentioning
confidence: 92%